Desestabilizando sociabilidades em uma sala de aula de língua inglesa de uma escola pública - Hoelzle, Maria José Lacerda Rodrigues (2016)
Much of the discourse concerning English teaching as a foreign language in the public school deals with failure. The reasons given range from problems with human resources, such as poor teacher training and students without basic literacies for language learning (JORDÃO, 2010), to structural and financial factors. In this scenario, I believe that, when we, as English teachers, merely have linguistic goals, regardless of the discursive ones, the sense of failure and impotence intensifies. Therefore, I sought to do a study, grounded on Critical Applied Linguistics, in a 6th grade classroom at a public school in Goiânia in order to create engagement moments and to destabilize sociabilities, understood as discursive positions (MOITA LOPES; FABRÍCIO, 2013), which have been crystallized over time in relation to issues such as family, race, gender and social classes. I worked as a teacher researcher and my aims were to analyze: 1) 6th grade students’engagement in critical English classes at a public school; 2) the destabilization moments during interactions driven by the activities proposed; 3) my experience with the critical work. This study is based on postmodernism to demonstrate how truths and totalities went through a crisis and how it was reflected in questions of knowledge, reaching the curricular studies. In this sense, this study was guided by theorizations about curriculum (SILVA, 2000; PARAÍSO, 2004; HENNING, 2009; LOPES, 2013) and critical literacy and multimodalities as new possibilities for language teaching in Brazil (COPE; KALANTZIS, 2005; MENEZES DE SOUZA, 2011; DUBOC, 2012; JORDÃO, 2013; ZACCHI, 2014).The participants who took part in this study were 11 male students and 7 female students, and the data were generated in 25 classes in the second half of 2014. The research instruments were questionnaires, audio-recording of classroom interactions, students’ work, a diary written by me and a final interview. The research is qualitative and is configured as a case study of autoethnographic nature. In the analysis, I could see that most students demonstrated greater engagement in activities of visual and multi-modal meanings, as well as in collective productions. In regard to the destabilizing moments, they occurred discreetly, given the power of crystallized speeches on the topics focused on. Concerning my practice, I believe I could cause destabilization moments, but on several occasions, I perpetuated hegemonic standards or failed to discuss important issues, which I believe to be part of this critical work that I am learning to construct. With regard to oral and written issues, I realized that, even resorting to Portuguese during the oral practice, it is possible to instigate students to think about social issues in English. The use of English language occurred more broadly in individual written assignments. By comparing the positions of the group at the beginning and at the end of the study, I realized that most participants showed satisfaction when dealing with critical issues during English classes. Moreover, most of them realized that "learning" the target language and "discussing" social aspects can happen simultaneously. Overall, the analysis suggests that a critical work can be done in basic education with promising results.